2019
DOI: 10.3389/fnins.2019.00493
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Spatial and Temporal Patterns of Cell Death, Glial Proliferation, and Blood-Brain Barrier Dysfunction Around Implanted Intracortical Neural Interfaces

Abstract: Improving the long-term performance of neural electrode interfaces requires overcoming severe biological reactions such as neuronal cell death, glial cell activation, and vascular damage in the presence of implanted intracortical devices. Past studies traditionally observe neurons, microglia, astrocytes, and blood-brain barrier (BBB) disruption around inserted microelectrode arrays. However, analysis of these factors alone yields poor correlation between tissue inflammation and device performance. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 94 publications
(138 reference statements)
7
82
0
Order By: Relevance
“…Similarly, cortical implants also resulted in chronic gliosis of microglial and astrocytic origins (Griffith and Humphrey, 2006;Rosskothen-Kuhl et al, 2018). Consistent with these observations, another study revealed a more elaborated spatial and temporal neuroinflammatory cascade, characterized by neuronal and progenitor cell loss, axonal and myelin reassembly, microglia and astrocyte reactivity, and pericyte deficiency-driven bloodbrain barrier disruption, both acutely and chronically around implanted devices (Wellman et al, 2019). Interestingly, the density of neural tissues and the implanted probes as well as the size and fixation method of the implants play an important role in determining the extent of microglia and astrocyte reaction with regions with high-density probes exhibiting more pronounced neuroinflammation (Thelin et al, 2011;Lind et al, 2012) while the numbers of implanted devices did not appear to affect glial cell scarring (Lind et al, 2013).…”
Section: Aberrant Immunological Activationsupporting
confidence: 57%
“…Similarly, cortical implants also resulted in chronic gliosis of microglial and astrocytic origins (Griffith and Humphrey, 2006;Rosskothen-Kuhl et al, 2018). Consistent with these observations, another study revealed a more elaborated spatial and temporal neuroinflammatory cascade, characterized by neuronal and progenitor cell loss, axonal and myelin reassembly, microglia and astrocyte reactivity, and pericyte deficiency-driven bloodbrain barrier disruption, both acutely and chronically around implanted devices (Wellman et al, 2019). Interestingly, the density of neural tissues and the implanted probes as well as the size and fixation method of the implants play an important role in determining the extent of microglia and astrocyte reaction with regions with high-density probes exhibiting more pronounced neuroinflammation (Thelin et al, 2011;Lind et al, 2012) while the numbers of implanted devices did not appear to affect glial cell scarring (Lind et al, 2013).…”
Section: Aberrant Immunological Activationsupporting
confidence: 57%
“…The use of ketamine, a known NMDA antagonist and GABA A potentiator, likely modulated the baseline probability of neuronal activation and entrainment (Alkire, Hudetz, & Tononi, 2008; McGirr, LeDue, Chan, Xie, & Murphy, 2017; Michelson & Kozai, 2018). Future studies should be conducted in awake preparations, taking particular care to consider the large influence on neuronal damage, microglial activation, and astroglia scarring, which are suggested to modulate both recording and stimulation (Alba, Du, Catt, Kozai, & Cui, 2015; Kozai, Alba, et al, 2014; Wellman, Li, Yaxiaer, McNamara, & Kozai, 2019). Additionally, there is a need to directly evaluate how stimulation‐induced activity changes over time in a chronic setting given the dynamic tissue responses to implantable electrodes and its effect on the excitatory‐inhibitory balance.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from mechanical failures ( Jorfi et al, 2015 ; Kozai et al, 2015a ), brain implants initiate and perpetuate local inflammatory processes which culminate in the formation of encapsulating scar tissues around the implant. This foreign body response (FBR) obstructs recording and stimulation qualities ( Gray et al, 1995 ; Rousche and Normann, 1998 ; Kipke et al, 2003 ; Nicolelis et al, 2003 ; Wellman et al, 2019 ). The prevailing views attribute these obstructions to the convergence of three main mechanisms: (I) the displacement of neurons away from the electrode surface by the progressive increase in the thickness of the glial scar ( Polikov et al, 2005 ; Salatino et al, 2017a ); (II) insulation of the electrodes from the neurons by the high electrical resistivity of the scar tissue and a self-assembled biofouling layer at the electrode surface ( Johnson et al, 2005 ; Polikov et al, 2005 ; Otto et al, 2006 ; Williams et al, 2007 ; Sommakia et al, 2009 , 2014 ; Prasad and Sanchez, 2012 ; Malaga et al, 2016 ); (III) reduced excitability, synaptic connectivity ( Vezzani and Viviani, 2015 ; Salatino et al, 2017b , 2019 ), and demyelination ( Winslow and Tresco, 2010 ; Winslow et al, 2010 ) of the neurons in the vicinity of the implant.…”
Section: Introductionmentioning
confidence: 99%